On fractional Pennes bio-heat equation using Legendre collocation method - Arvind Kumar Mishra; Sushil Kumar; Ajay Kumar Shukla (International Journal of Mathematics for Industry)
In this paper, the distribution of heat in skin tissue during thermal treatment using the time-fractional Pennes model is studied. Temperature variations concerning several parameters such as derivative [Formula: see text] time, blood perfusion, and transmitted power are described using the Legendre collocation technique. The best feature of the proposed technique is the conversion of fractional-order differential equations into a set of algebraic systems and the ability to approximate both spatial and temporal coordinates with a single basis. The obtained results and comparison with an exact solution are illustrated.